Vilka faktorer påverkar privata skogsägares val av skoglig samarbetspartner? - Jonsson, Axel (2016)
This study's goal is to look into what kind of factors that affect which forestry partner the private forest owners choose. This work is a cooperation with Mellanskog and will help them to get knowledge about what the private forest owners are searching for in their forestry partner. An opinion poll has been done in the northeast area of Hälsingland, Sweden. 200 surveys were sent out to private forest owners that were selected at random. The questions in the survey was about what kind of forest owner they are and what valuations they had around owning forest. The result showed that most of the forest owners in the northeast area of Hälsingland are men in or over the age of 50. They´ve got 50 hectares or more productive forest land and most of them live in the same area as their real estate is located. The most common motive to own forest land is for the financial returns and managing previous generations legacy. Most of the forest owners are looking for a forestry partner with good competence and reliability.